Pengaruh Pengetahuan, Sikap, dan Norma Subjektif terhadap Keputusan Pembelian Kosmetik Perawatan Wajah Berlabel Halal pada Mahasiswa/i di Jawa Barat: Halal Industry - Miskal, Miskal Kholiq; Anita Priantina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to investigate the factors affecting the purchasing choices of halal-certified facial care cosmetics, specifically focusing on the roles of knowledge, attitude, and subjective norm. The participants in this research are students residing in West Java who actively use halal-certified facial care products. Data collection is carried out through online surveys, gathering responses from a total of 100 participants. Hypothesis testing is performed utilizing Smart PLS 3.0 software. The findings reveal that both attitude and knowledge exhibit significant impacts on purchasing decisions, whereas subjective norm does not demonstrate a significant influence on these decisions.